Rheology of self-nucleated poly(ɛ-caprolactone) melts. (February 2018) - Sangroniz, L.; Barbieri, F.; Cavallo, D.; Santamaria, A.; Alamo, R.G.; Müller, A.J.
Graphical abstract: Highlights: The rheological properties of self-nucleated and homogeneous polycaprolactones melts investigated. Increase in Newtonian viscosity and flow activation energy of self-nucleated melts. Apparent decrease of the molecular weight between entanglements. Differences in the rheological behavior attributed to interactions in the self-nuclei. Abstract: This work presents novel findings on the rheological properties of self-nucleated polymer melts. Different polycaprolactones (PCL) with varying molar masses were investigated with shear rheometry, assessing the viscoelastic functions at different temperatures, reached either from the melt or from the semi-crystalline state. The latter condition produces a self-nucleated melt, in which residual clusters of unclear nature enhance the re-crystallization process, while a homogeneous melt is obtained with the first protocol. Striking differences are observed in melts with or without self-nuclei. The Newtonian viscosity and flow activation energy increase up to one order of magnitude with respect to the fully equilibrated melt. The plateau modulus also shows a remarkable increment, indicating an apparent decrease of the molecular weight between entanglements. The results demonstrate the existence of an additional attractive intermolecular interaction between chain segments in self-nucleated PCL melts, able to provide "extra" physical entanglements which progressively dissolve as the temperature is raised. Self-nucleated propene/ethylene copolymers analyzed in previous work display much weaker effects. The apparent discrepancy is discussed in light of the differences in intermolecular interactions and melting enthalpies between the two polymers.